2006
DOI: 10.1007/s00213-006-0487-z
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in drug abuse vulnerability: d-Amphetamine and sensation-seeking status

Abstract: Rationale-While the personality dimensions of novelty seeking and sensation seeking are associated with drug abuse vulnerability, the mechanisms associated with this vulnerability remain obscure.Objective-This study examined the behavioral effects of d-amphetamine in healthy volunteers scoring in the upper and lower quartiles based on age-and gender-adjusted population norms on the impulsive Sensation-Seeking Scale (SSS) of the Zuckerman-Kuhlman personality questionnaire (ZKPQ).Method-Participants completed 7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
106
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 50 publications
12
106
1
2
Order By: Relevance
“…All volunteers reported use of stimulant drugs (e.g., caffeine, nicotine, or amphetamine) prior to their participation in this experiment. This inclusion criterion was selected based on previous human behavioral pharmacology research in which oral damphetamine was administered (Fillmore et al, 2005;Kelly et al, 2006;Stoops et al, 2006). Two additional volunteers completed the experiment, but failed to respond for d-amphetamine or placebo on the modified progressive-ratio procedure under any condition.…”
Section: Volunteersmentioning
confidence: 99%
“…All volunteers reported use of stimulant drugs (e.g., caffeine, nicotine, or amphetamine) prior to their participation in this experiment. This inclusion criterion was selected based on previous human behavioral pharmacology research in which oral damphetamine was administered (Fillmore et al, 2005;Kelly et al, 2006;Stoops et al, 2006). Two additional volunteers completed the experiment, but failed to respond for d-amphetamine or placebo on the modified progressive-ratio procedure under any condition.…”
Section: Volunteersmentioning
confidence: 99%
“…Specifically, impulsivity was distinct from sensationseeking, thus failing to support any suggestion that impulsivity was intrinsically related to this concept (e.g. Acton, 2003;Depue & Collins, 1999;Kelly et al, 2006;Moeller et al 2002;Sher & Trull, 1994;Zuckerman et al, 1993) and/or was an adult-form of sensation-seeking (Clayton, Segress & Caudill, 2007). Thus, in samples where there are known to be increased levels of sensation-seeking and impulsivity (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…It is closely related to other personality constructs associated with substance use, such as impulsivity (e.g. Acton, 2003;;Ersche, et al, 2010;Moeller et al 2002), openness to experience and extraversion (Grekin, Sher & Wood, 2006), with considerable cross-over across these constructs (Depue & Collins, 1999;Kelly et al, 2006;Sher & Trull, 1994;Zuckerman et al, 1993). For example, some researchers have suggested that extraversion is an indirect test of sensation-seeking (Sher & Trull, 1994), with impulsivity a reconceptualised 'adult' form of sensation-seeking (Clayton, Segress & Caudill, 2007).…”
mentioning
confidence: 99%
“…ROIs were identified on the basis of our hypotheses (see Introduction), in combination with prior functional imaging studies that examined differences in neural processing between groups of high and low selfreported sensation-seekers during decision-making and emotional processing tasks (Abler et al, 2006;Joseph et al, 2009;Freeman and Beer, 2010;Straube et al, 2010;Kruschwitz et al, 2012). These ROIs consisted of the vmPFC, vS, and insula.…”
Section: Discussionmentioning
confidence: 99%
“…Such common value coding might explain why intense sensory experiences are powerful positive motivators for high sensation-seeking individuals. When economic value for other types of choice has been investigated in the past, BOLD signal in the vmPFC and vS has been identified as representing the expected value of options (Knutson et al, 2001;Abler et al, 2006;Levy and Glimcher, 2012;Clithero and Rangel, 2014) and even valued memories of past experiences (Speer et al, 2014). Although the interpretation of these results has been questioned (Hayden and Heilbronner, 2014;O'Doherty, 2014), the vmPFC in particular has been identified in analyses probing common representation across numerous different kinds of rewards (Levy and Glimcher, 2012;Clithero and Rangel, 2014), indicating that this region may be involved in computations using a common value currency.…”
Section: Introductionmentioning
confidence: 99%